2018
DOI: 10.1016/j.celrep.2018.10.055
|View full text |Cite
|
Sign up to set email alerts
|

KDEL Receptors Are Differentially Regulated to Maintain the ER Proteome under Calcium Deficiency

Abstract: Highlights d A mass departure of ER-resident proteins occurs in response to ER calcium depletion d KDELR2 and KDELR3, but not KDELR1, are unfolded protein response genes d KDELR2 and KDELR3 upregulation by ER calcium loss counteracts ER protein loss d Stabilizing calcium and increasing KDEL receptor expression have therapeutic potential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(186 citation statements)
references
References 66 publications
9
176
0
1
Order By: Relevance
“…However, some cellular and proteomic analyses have identified additional targetssuch as histones and cytosolic Hsp70 and Hsp40 family chaperones -that localize to cellular compartments other than the ER [30], [31], [40]. How HYPE interacts physiologically with these non-ER localized proteins is unclear [54], though a recent report reveals that a mass exodus of ER resident proteins occurs in response to ER Ca 2+ depletion [41]. Additionally in C. elegans, HYPE is reported to be partially present in the cytosol in addition to the ER lumen [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, some cellular and proteomic analyses have identified additional targetssuch as histones and cytosolic Hsp70 and Hsp40 family chaperones -that localize to cellular compartments other than the ER [30], [31], [40]. How HYPE interacts physiologically with these non-ER localized proteins is unclear [54], though a recent report reveals that a mass exodus of ER resident proteins occurs in response to ER Ca 2+ depletion [41]. Additionally in C. elegans, HYPE is reported to be partially present in the cytosol in addition to the ER lumen [29].…”
Section: Discussionmentioning
confidence: 99%
“…The KDEL receptor is a seven-transmembrane-domain protein whose function is to 294 sort and retrieve proteins bearing a KDEL sequence (calnexin, GRP78, PDI, for instance) and 295 possibly proteins with KDEL-like sequences (Erp72, MANF and CDNF) from the Golgi 296 complex to the ER/SR (Dorner et al, 1990;Voutilainen et al, 2015;Becker et al, 2016). The 297 importance of KDEL-R to cardiomyocyte homeostasis was demonstrated by studying 298 transgenic mice that express a mutant KDEL-R in which reverse transport from Golgi to 299 ER/SR was compromised.…”
Section: Kdel-r In the Membrane Binds Cdnf And Mediates Its Cardiopromentioning
confidence: 99%
“…Recent studies, however, have suggested that the KDEL-R has additional functions 301 and new cellular localizations, including the plasma membrane. In this regard, there is 302 mounting evidence for the presence of KDEL-R at the surface of mammalian cells, where the 303 receptor binds cargo proteins such as A/B microbial toxins K28, MANF and other proteins in 304 which a KDEL-sequence is present at the C-terminus (Riffer et al, 2002;Henderson et al, 305 2013;Becker et al, 2016;Trychta et al, 2018). Trychta and collaborators (2018) have coined 306 the term "ER exodosis" in an elegant study where they showed a massive departure of proteins 307 containing KDEL-related sequences upon calcium-induced ER-stress in several mammalian 308 cell lines.…”
Section: Kdel-r In the Membrane Binds Cdnf And Mediates Its Cardiopromentioning
confidence: 99%
See 1 more Smart Citation
“…The KDEL-Receptors (KDELRs) are a family of seventransmembrane-domain ER protein retention receptors consisting of three members (KDELR1, 2 and 3) that function in the ER Stress Response (ERSR). They share structural homology, but each isoform can have different ligands 18,19 . They are responsible for the retrograde transport of protein machinery from the Golgi to the ER, including chaperones that target unfolded proteins for refolding, and whose disassociation from membrane receptors stimulates UPR signaling 19,20 .…”
mentioning
confidence: 99%